2010
DOI: 10.20870/oeno-one.2010.44.4.1473
|View full text |Cite
|
Sign up to set email alerts
|

It is possible to predict Sangiovese wine quality through a limited number of variables measured on the vines

Abstract: <p style="text-align: justify;"><strong>Aims</strong>: The research work aimed at creating and testing a method to evaluate vine performance of Sangiovese (VPS), in particular, a method able to predict the potential oenological result through a limited number of variables measured on the vines.</p><p style="text-align: justify;"><strong>Methods and results</strong>: A matching table was created on the basis of literature and the experience acquired over twenty years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 7 publications
(4 reference statements)
1
16
0
Order By: Relevance
“…Therefore, in addition to the well-established effects due to nitrogen limitation, we suggest that the reduced availability of nitrogen and sulfate in BRO12 soil might have reduced the GSH levels in berries and increased the amount of phenolic compared to the grapes deriving from BRO11 site. This hypothesis is also consistent with the overall VPS values related to wine quality (BRO11 = 62, BRO12 = 81) determined in our previous work (Costantini et al, 2013), as one of the main parameters used to calculate the VPS values is the phenolic compounds content (Bucelli et al, 2010; Figure 7).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, in addition to the well-established effects due to nitrogen limitation, we suggest that the reduced availability of nitrogen and sulfate in BRO12 soil might have reduced the GSH levels in berries and increased the amount of phenolic compared to the grapes deriving from BRO11 site. This hypothesis is also consistent with the overall VPS values related to wine quality (BRO11 = 62, BRO12 = 81) determined in our previous work (Costantini et al, 2013), as one of the main parameters used to calculate the VPS values is the phenolic compounds content (Bucelli et al, 2010; Figure 7).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the grapes of BRO12 showed a small increase of the average sugar content (23.2 • Brix, instead 22.2 • Brix of BRO11), extractable polyphenols (1,883 vs. 1,638 mg•l −1 ) and significantly (p < 0.05) higher total anthocyanins (1,500 vs. 1,316 mg •l −1 , data available only for 2008 and 2009). The overall wine quality was determined by means of the "Vine Performance of Sangiovese" (VPS) index (Bucelli et al, 2010), which showed a higher VPS value (VPS = 81) in BRO12 than in BRO11 (VPS = 62) over the three vintages.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The values for measured parameters were considered suitable for the current target enological model of Sangiovese wines (Bucelli et al 2010). The differences in composition between groups a and b (2003 harvest) were determined by the characteristics of the soil.…”
Section: Characterization Of Grapesmentioning
confidence: 99%
“…The effect of these environmental factors on grape composition has been reported (Cohen and Kennedy 2010). The composition of grapes harvested on 20 Sept and 5 Oct was considered slightly suitable for Sangiovese wines, whereas the composition of grapes harvested on 19 Oct was considered more suitable (Bucelli et al 2010). .…”
Section: Characterization Of Grapesmentioning
confidence: 99%
“…1). It displays the pedological and climatological characteristics best suited for the production of quality wines [Bucelli et al, 2010]. The average dimension of the vineyards is about 4 hectares, a surface representative of many other Tuscan estates located in hilly, often steeply sloping areas.…”
Section: Test Area and Datamentioning
confidence: 99%